Morphological alterations of cultured human colorectal matched tumour and healthy organoids - Mohammad, Seyed; Kashfi, Hossein; Almozyan, Sheema; Jinks, Nicholas; Koo, Bon-Kyoung; Nateri, Abdolrahman Shams (Impact Journals, 2018)
Organoids have extensive applications in many fields ranging from modelling human development and disease, personalised medicine, drug screening, etc. Moreover, in the last few years, several studies have evaluated the capacity of organoids as transplantation sources for therapeutic approaches and regenerative medicine. Nevertheless, depending on the origin of the cells and anatomical complications, an organoid transplant may make tissue regeneration difficult. However, some essential aspects of organoids including the morphological alterations and the growth pattern of the matched tumour and their healthy derived organoids have received less attention. Therefore, the current work focused on culturing matched healthy and tumour organoids from the same patient with colorectal cancer (CRC) and assessed their timed growth and structural differences on a daily basis. The healthy organoids underwent proliferation and branching morphogenesis, while the tumour organoids did not follow the same pattern, and the majority of them developed cystic structures instead. However, the number and size of tumour organoids were different from one patient to another. The differential morphological changes of the healthy versus human colonic tumour organoids likely linked to distinct molecular and cellular events during each day. Thus, while their specific structural features provide valuable in vitro models to study various aspects of human intestinal/colon tissue homeostasis and CRC which avoid or replace the use of animals in research, this model may also hold a great promise for the transplantation and regenerative medicine applications.